BS IEC 63098-3. Transmitting equipment for radiocommunication. Radio-over-fibre technologies and their performance standard. Part 3. Radio over fibre based remote radar for foreign object and debris (FOD) detection system (23rd October 2020) - British Standards Institution,
No abstract available